Performance Activities and Match Outcomes of Professional Soccer Teams during the 2016/2017 Serie A Season - Longo, Umile Giuseppe; Sofi, Francesco; Candela, Vincenzo; Dinu, Monica; Cimmino, Matteo; Massaroni, Carlo; Schena, Emiliano; Denaro, Vincenzo (Medicina (Kaunas, Lithuania), 2019)
Background and Objectives: Soccer is the most popular sport in the world. To describe athletic performance, match statistics, and their relationships with the probability of achieving the first positions of the final ranking in the Italian football league “Serie A”, season 2016/2017. Materials and Methods: Analyses comprised all the matches played by the 20 teams of the “Serie A” championship during the season 2016–2017. Indicators of athletic performance (total distance covered in km, jogging, running and sprint activities, and average speed) and match statistics (total shots, shots on target, goal attempts, assists, turnovers, and steals) were obtained from the Italian football league. Results: Analyses of performance activities according to the final ranking showed no significant differences for the total distance covered and speed, while a statistically significant difference (p < 0.05) among teams was observed for jogging, running and sprint activities. In regard to match statistics, all the parameters investigated were significantly different among the teams. By grouping teams into four subgroups (those who qualified for the Champions League, those who qualified for the Europe League, those who ranked intermediate positions and those who relegated from the “Serie A” league), the percentage of jogging, running and sprint activities, as well as match statistics were significantly different among groups, with a downward trend for total shots, shots on target, goal attempts, assists, and turnovers. The logistic regression analysis revealed that sprint activities as well as total shots, shots on target, goal attempts, and assists higher than the 3rd tertile of their distribution were associated with a higher probability of reaching the first three positions of the final ranking. Conclusions: An increased probability to achieve the first positions of the final ranking in the Italian football league “Serie A” seemed to be mainly related to sprint activity, goal attempts, total shots, shots on target and assists.